Pengaruh Kompetensi Terhadap Kinerja Auditor Pada Inspektorat Jenderal Kementerian Pertanian - Safrizal; Pandoyo; Neli Marita (JURNAL ILMU ADMINISTRASI PUBLIK DAN BISNIS, 2020)
The purpose of this research is to find out the influence of competence on the Inspectorate General of the Ministry of Agriculture, which consists of Motives (Desire), Traits (Physical Characteristics), Self-Concept (attitude), Skills (ability), Knowledge. And to analyze the quality of the examination process, skills, (abilities). This research was conducted in the office of inspectorate general of the Ministry of Agriculture South Jakarta with a sample of 50 people taken proportionate Stratified Random Sampling Research method used in this research is descriptive research method. Data analysis used is descriptively quantitated to explain research data and research description, while to analyze quantitative data using calculation formula SPSS. The results of the study proved that simultaneously the results of this study proved the alleged hypothesis H0 was rejected and H1 accepted that what the authors did was found for correlation analysis obtained r = 0.835, for the Determinant Coefficient obtained 69.7%. As for the test – t obtained the result of t calculate > t table = 5,398 > 2,021. Then Ho is rejected and Ha is accepted. Based on the results of the study found that there is a significant influence of competence on the performance of auditors in the Inspectorate General of the Ministry of Public Works.